Communicating as women in STEM - Brammer, Charlotte (Academic Press, an imprint of Elsevier, 2018)
Communicating as Women in STEM discusses various communication styles, also demonstrating how principles can be applied during interpersonal interactions in day-to-day environments. It provides women and other underrepresented groups, faculty and administrators with the tools they need to break barriers raised by different communication styles within the STEM fields. Sections cover tactics on how to become more aware of communication patterns and how to cope with, and improve, communication. This practical resource for women in the STEM fields is also ideal for mentors, educators, advisers and organizations interested in encouraging women to choose and remain in these fields. Enables women, minorities, faculty and administrators to develop broader communication skills. Teaches constructive communication strategies for interaction with mentees, mentors, faculty, managers, colleagues and other professionals. Contains observation exercises that include questions and sample scenarios to illustrate communication strategies.